T-Cell Acute Lymphoblastic Leukemia in a Young Adult With Thrombocytopenia-absent Radius Syndrome: A Case Report and Review of the Literature. Issue 6 (August 2021) - Beauvais, David; Cabannes-Hamy, Aurélie; Leblanc, Thierry; Dhédin, Nathalie; Magda, Alexis; Cuccuini, Wendy; Clappier, Emmanuelle; Vial, Yoann; Boissel, Nicolas
Abstract : Thrombocytopenia-absent radius (TAR) syndrome is a rare inherited bone marrow failure syndrome not generally associated with acute leukemia. The authors report a case of T-cell acute lymphoblastic leukemia in an adult female individual newly diagnosed with TAR syndrome. A 347-kb microdeletion of chromosome 1q21.1 involving the RBM8A gene was detected within a gain of whole chromosome 1. Next-generation sequencing on fibroblasts confirmed germline heterozygous deletion of RBM8A but on the other allele, noncoding low-frequency regulatory single-nucleotide polymorphism of RBM8A (rs139428292; rs201779890) were not found. The tolerance of the treatment was unusual and mostly marked by a slow hematopoietic recovery leading to a 6-month delay at the beginning of the maintenance phase. Only 5 cases of acute leukemia were reported in patients with TAR syndrome in the literature: 4 acute myeloid leukemia and one B-cell acute lymphoblastic leukemia. This is the first report of T-cell acute lymphoid leukemia occurring in the context of TAR syndrome.